Pendampingan Literasi Bahasa Inggris Komunitas Anak Kampung Walal (KAWAL) di Kabupaten Sorong - Eddy saputro, isnaini; Faizin, Muhammad (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
In the 21st century, the acquisition of English as a second language is very important for a group of children in Walal Village who are currently studying at elementary school. This is useful for supporting 6 skills of 21st century education, namely critical thinking, communication, creativity, collaboration, culture and connectivity. Walal Village is one of the model villages in Sorong Regency which has a high enthusiasm for creating the latest breakthroughs, especially in the field of education. Walal Village is located in Salawati District which must be traveled 35 kilometers from Sorong City. Thus, access to information related to education is very limited for children in Walal Village. In this case, students of the Community Service Lecture (KPM) at the Muhammadiyah Sorong Education University provided one month of English literacy assistance for the children of Kampung Walal community. The aim of this assistance is an effort to empower Human Resources (HR) through a community empowerment program for English language learning guidance. This English literacy assistance is very important to provide to Walal Village children who are already aware of the importance of English around them. This program is also related to the description of the Walal Village Government's vision and mission in developing human resources in terms of quality education. English literacy assistance includes acquiring English, processing language in the form of remembering and memorizing words or terms, and understanding meanings that can be applied to listening, reading, speaking and writing skill activities. The efforts of this English literacy assistance are to change the mindset of the children of Walal Village that learning English is fun, regardless of age, and affordable. In fact, through mentoring, children in Walal Village experience changes in knowledge and attitudes during the English literacy process.